2001
DOI: 10.1016/s0148-2963(99)00039-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' trust of salesperson and manufacturer: an empirical study

Abstract: A positive model of consumers' trust of salesperson and manufacturer is developed which provides suggestions for improving relationships and increasing buyer ± seller trust. The findings indicate that buyer ± seller trust results from salesperson competence, lowpressure selling tactics, service quality, manufacturer ethical concern, and a general tendency to trust others. Product familiarity acts to decrease the overall trust of the salesperson. Manufacturer trust is fostered by satisfaction with the ownership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
205
1
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(229 citation statements)
references
References 46 publications
9
205
1
11
Order By: Relevance
“…Gruber et al (2006) found competence to be the most desired attribute of customer contact employees within complaint handling encounters. These findings are also aligned with sales management research where "Competence", as a function of salesperson behaviour, has been found to be a determinant of customer trust (Kennedy, Ferrell & Leclair, 2001;Swan, Bowers & Richardson, 1999). British students believe that when trust exists between them and the professor, it translates into better academic performance ("Performance"), which in turn leads to a better start for their careers.…”
Section: Service Recovery Expectations Of British Students (Ladderingsupporting
confidence: 78%
“…Gruber et al (2006) found competence to be the most desired attribute of customer contact employees within complaint handling encounters. These findings are also aligned with sales management research where "Competence", as a function of salesperson behaviour, has been found to be a determinant of customer trust (Kennedy, Ferrell & Leclair, 2001;Swan, Bowers & Richardson, 1999). British students believe that when trust exists between them and the professor, it translates into better academic performance ("Performance"), which in turn leads to a better start for their careers.…”
Section: Service Recovery Expectations Of British Students (Ladderingsupporting
confidence: 78%
“…In fact, consumer trust in a company's activities is highly dependent on the extent to which s/he disapproves the firm's ethical practices relating to product, price, distribution, and promotion (Lagace et al, 1991;Robertson and Anderson, 1993). A positive association between the firm's marketing ethicality and consumer trust was confirmed by various studies (e.g., Beatty et al, 1996;Bejou et al, 1998;Kennedy et al, 2001;Román and Ruiz, 2005). Conversely, consumers with more negative ethical perceptions of a firm's marketing activities were found to put less trust in a particular firm (Creyer and Ross, 1997;Hosmer, 1995;Nebenzahl et al, 2001).…”
Section: Marketing Unethicality and Consumer Trustmentioning
confidence: 95%
“…Findings from Naser and Mountinho (1997) suggest that Islamic ethical sales practices, as perceived by financial services customers, increased customer trust in the CRA. Likewise, different exploratory studies in the conventional field have shown that customer trust in the salesperson can be earned by the honest actions of sales representatives (Swan et al, 1985;Swan et al, 1988;Beatty et al, 1996), as well as low-pressure selling techniques (Strutton et al, 1996;Kennedy et al, 2001).…”
Section: Customer Trust In the Islamic Bankmentioning
confidence: 99%